Examining Online Purchase Intention in E-Commerce: The Effects of Knowledge, Attitude, Subjective Norms, and Perceived Behavioral Control - Selvia Putri Anggraini; Suswadi; Kusriani Prasetyowati; Adhisty Puri Damayanti (Journal of Rural and Urban Community Studies, 2026)
The development of technology has encouraged Indonesian consumers to increasingly use e-commerce platforms to purchase their daily necessities. This study aims to analyze the effect of knowledge, attitudes, subjective norms, and perceived behavioral control on consumers’ intention to shop online through e-commerce. This research applied a causal-comparative approach. The study was conducted in Greater Jakarta (Jabodetabek), Semarang, Yogyakarta, and Solo Raya. A total of 100 respondents were selected using a non-probability sampling method, specifically purposive sampling. Data were collected through interviews using structured questionnaires. The research instruments were tested, and the data were analyzed using SmartPLS 3 software with the Structural Equation Modeling (SEM) method. The results show that knowledge has a significant effect on consumers’ attitudes toward online shopping through e-commerce platforms.